Olanzapine for the treatment of ICU delirium: a systematic review and meta-analysis - Si Bo Liu; Shan Liu; Kai Gao; Guo Zhi Wu; Guo Zu; Jin Jie Liu (SAGE Publishing, 2023)
Background: As an atypical antipsychotic drug, olanzapine is one of the most commonly used drugs for delirium control. There are no systematic evaluations or meta-analyses of the efficacy and safety of olanzapine for delirium control in critically ill adults. Objectives: In this meta-analysis, we evaluated the efficacy and safety of olanzapine for delirium control in critically ill adults in the intensive care unit (ICU). Data Sources and Methods: From inception to October 2022, 12 electronic databases were searched. We retrieved randomized controlled trials (RCTs) and retrospective cohort studies of critically ill adults with delirium that compared the effects of olanzapine and other interventions, including routine care (no intervention), nonpharmaceutical interventions and pharmaceutical interventions. The main outcome measures were the (a) relief of delirium symptoms and (b) a decrease in delirium duration. Secondary outcomes were ICU and in-hospital mortality, ICU and hospital length of stay, incidence of adverse events, cognitive function, sleep quality, quality of life, mechanical ventilation time, endotracheal intubation rate and delirium recurrence rate. We applied a random effects model. Results: Data from 10 studies (four RCTs and six retrospective cohort studies) involving 7076 patients (2459 in the olanzapine group and 4617 in the control group) were included. Olanzapine did not effectively relieve delirium symptoms (OR = 1.36, 95% CI [0.83, 2.28], p  = 0.21), nor did it shorten the duration of delirium [standardized mean difference (SMD) = 0.02, 95% CI [−1.04, 1.09], p  = 0.97] when compared with other interventions. Pooled data from three studies showed that the use of olanzapine reduced the incidence of hypotension (OR = 0.44, 95% CI [0.20, 0.95], p  = 0.04) compared with other pharmaceuticals. There was no significant difference in other secondary outcomes, including ICU or hospital length of stay, in-hospital mortality, extrapyramidal reactions, QTc interval prolongation, or overall incidence of other adverse reactions. The number of included studies was not sufficient for performing a comparison between olanzapine and no intervention. Conclusion: Compared with other interventions, olanzapine has no advantage in alleviating delirium symptoms and shortening delirium duration in critically ill adults. However, there is some evidence that the rate of hypotension was lower in patients who received olanzapine than in those who received other pharmaceutical interventions. There was a nonsignificant difference in the length of ICU or hospital stay, in-hospital mortality, and other adverse reactions. This study provides reference data for delirium research and clinical drug intervention strategies in critically ill adults. Registration: Prospective Register of Systematic Reviews (PROSPERO; registration number CRD42021277232).